A manikin-based simulation study of a dispatch operator directed CPR algorithm within the Western Cape setting and the self- reported comfort around its execution - De Caires, Leonel Paulo (Division of General Surgery, 2022)
Background: There is little data in Africa regarding dispatch guided telephonic CPR. This study looks at the quality of CPR performed when compared to AHA guidelines, by untrained laypersons when given telephonic CPR instructions using the Western Cape EMS Guidecards algorithm for telephone assisted CPR. Methods: In this prospective observational, simulation study, participants were given telephonic hands-only CPR instructions using the Western Cape EMS Guidecards. CPR quality (hand placement, rate, depth and chest recoil) was analysed and then followed by a questionnaire looking at the self-reported comfort regarding the execution of said instructions. Results: Overall quality of CPR by participants (n=50) was suboptimal with no participant complying with current CPR guidelines. Demographic factors influenced quality where males pushed on average deeper (40.8mm vs 28.5mm, p=0.004) when compared to females. Correct hand placement and chest exposure were directly related to the caregivers' home language with English making it more likely to correctly perform these instructions (p=0.01 and p=0.002, respectively). Self-reported comfort had no effect on executed CPR quality. Conclusion: The quality of CPR performed by laypersons, when directed by a call-taker using the Western Cape Provincial EMS Guidecards Algorithm, can be suboptimal in terms of compression rate, depth, full chest recoil and baring of the chest. There is an urgent need to find more effective ways, in the Western Cape EMS, to improve executed CPR quality when guided by a trained telephone operator.